2014
DOI: 10.1103/physreva.90.032315
|View full text |Cite
|
Sign up to set email alerts
|

Quantum correlations in a noisy neutron interferometer

Abstract: We investigate quantum coherences in the presence of noise by entangling the spin and path degrees of freedom of the output neutron beam from a noisy three-blade perfect crystal neutron interferometer. We find that in the presence of dephasing noise on the path degree of freedom the entanglement of the output state reduces to 0, however the quantum discord remains nonzero for all noise values. Hence even in the presence of strong phase noise nonclassical correlations persist between the spin and the path of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Neutron interferometers have been used to demonstrate single-particle entanglement between different degrees of freedom, such as spin + path and spin + energy, and have supported extensive studies of quantum contextuality [23][24][25][26][27]. A useful measure of entanglement for a bipartite quantum system is the concurrence [28][29][30], which is equal to 1 when the entanglement is maximum and 0 when the state is separable.…”
Section: A Characterizing the Spin-orbit Statesmentioning
confidence: 99%
“…Neutron interferometers have been used to demonstrate single-particle entanglement between different degrees of freedom, such as spin + path and spin + energy, and have supported extensive studies of quantum contextuality [23][24][25][26][27]. A useful measure of entanglement for a bipartite quantum system is the concurrence [28][29][30], which is equal to 1 when the entanglement is maximum and 0 when the state is separable.…”
Section: A Characterizing the Spin-orbit Statesmentioning
confidence: 99%
“…9) surround the neutron guides for radiation safety and to minimize backgrounds. The interferometer is supported by a rotation 8 , translation 9 and height Systematic uncertainties of calibrated fission chamber owing to the deposit particulars are estimated to be ≈ 10 %. Fluence rates for both NIOFa and NIOF included neutrons with wavelengths λ/n where n = 2, 3, .…”
Section: Niofa Monochromatormentioning
confidence: 99%
“…neutron phase effects (see Table 1). fisherThese include demonstration of the 4π periodicity of neutron wave function [3], precision coherent and incoherent scattering length measurements [4][5][6][7], measuring vertical coherence [8], demonstrating contrast in the presence of zero entanglement but non-zero Quantum Discord [9], and more applied experiments including phase contrast imaging [10,11] and measuring the density of thin films [12]. More recently, proposed experiments have needed both high neutron polarization and precise spin manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate this effect we considered a configuration where we entangled the spin and path degrees of freedom of the neutron by placing a spin-rotator in one path of the interferometer and then observed the output path contrast and spin contrast with and without postselected spin measurements [24]. In the absence of spin measurements, our theoretical calculations found that strong phase noise caused the entanglement to reduce to zero; however the quantum discord remained nonzero.…”
Section: Coherence and Qipmentioning
confidence: 99%